The relationship between isometric contraction durations during hold-relax stretching and improvement of hamstring flexibility - Bonnar, B. P.; Deivert, R. G.; Gould, T. E. (The Journal of Sports Medicine and Physical Fitness, 2004)
AIM: Previous research suggests proprioceptive neuromuscular facilitation (PNF) stretching techniques produce greater increases in range of motion than static or ballistic. The purpose of this study was to determine the isometric contraction hold time that best produces gains in hip range of motion after a 3-s (3-HR), 6-second (6-HR), and 10-s (10-HR) hold-relax PNF stretch. METHODS: The experimental design was a within subjects repeated measures 2 factor (baseline and treatment) by 3 factor (3-HR, 6-HR, 10-HR) ANOVA. The dependent variable was hamstring flexibility as measured in degrees of passive hip flexion with the knee extended. Measurements were taken in a university athletic therapy clinic. Sixty active individuals without history of knee or hip injury volunteered for this study. Each subject was randomly assigned to a 3-HR, 6-HR, or 10-HR group for the hold-relax PNF stretch. All subjects were passively taken to the end range of motion 3 times and a goniometric measurement was taken. Each subject then performed the hold-relax PNF stretch 3 times with either a 3-HR, 6-HR, or 10-HR isometric contraction hold time and another goniometric measurement was taken. An average of each of these 3 trials was then calculated. RESULTS: The data analysis revealed a significant main effect difference (F(1,5 7)+/-633.97, p<.001, eta2=0.918) between the baseline and treatment measurements. There were no significant differences for the between groups (3-HR, 6-HR, 10-HR) main effect or for the interaction term. CONCLUSIONS: All 3 hold-time conditions produced significant gains in range of motion compared to baseline measurements. The application of the findings suggest that clinicians could choose any of the hold-times and produce the same result to patient hip joint flexibility.